Modeling the effects of water temperature on the population dynamics of Galba viatrix and infection by Fasciola hepatica: a two-year survey in Andean Patagonia, Argentina - Soler, Paula (2024)
Background: The trematode parasite Fasciola hepatica (liver fluke) can infect livestock, wild mammals, and humans, generating serious economic losses worldwide. Aquatic or amphibious snails of the Lymnaeidae family are the intermediate host of this parasite. Both snail population dynamics and parasite development are closely associated with temperature, although most field studies have recorded air temperature rather than water temperature. Our aim was to statistically model the population dynamics of lymnaeid snails and their infection by F. hepatica under natural environmental conditions in Northwest Andean Patagonia. Methods: For two years, we sampled snails monthly in four bodies of water, while registering water and air temperature hourly, and assessing F. hepatica infection in snails. Hierarchical Bayesian modeling allowed us to estimate the functional relationship between water temperature and population growth, the probability of detecting snails, and infection by F. hepatica. Results: A total of 1,411 Galba viatrix snails were collected, identified, and analyzed for F. hepatica infection. All sites showed seasonal variation in the number of snails collected and in water temperature as well as sharp variations in snail counts between surveys adjacent in time. The hierarchical model revealed that water temperature acts, at least, at two different time scales: water temperature at the time of sampling determines snail detection probability, whereas the average water temperature between sampling dates affects lymnaeid population growth. We found maximum F. hepatica prevalences in snails of 40% (2/5 and 4/10), followed by 33% (65/197). These are the highest prevalences recorded in G. viatrix populations in Argentina to date. Our modeling evidenced that the positive effects of water temperature on infection probability increases with snail size and prevalence on the previous survey, while previous prevalence strongly enhances the effects of snail size. Conclusions: Our results underscore the high temporal and spatial variability in the population of snails and the prevalence of F. hepatica, as well as the major impact temperature has on detecting snails. Our models provide quantifications of the effects of water temperature on the population growth of G. viatrix, its detection, and infection under natural field conditions. These are crucial steps towards generating mechanistic models of F. hepatica transmission that would facilitate the design and simulation of potential interventions based on treatments and on environmental and livestock management, taking into account the specific characteristics of each region.